Kompetensi Profesional Guru Bimbingan dan Konseling Dalam Pelayanan Bimbingan dan Konseling - Suprihatin Suprihatin (JIGC (Journal of Islamic Guidance and Counseling), 2017)
Guidance and counseling is a process of assistance or assistance provided by counselor (counselor) to the individual (counselee) through face-to-face meetings or mutual relations between the two, so that the counselee has the ability or ability to see and find problems and be able to solve the problem itself. Guidance and counselor / counselor counselor in juridical in the National Education System is stated as one of the qualifications of educators parallel to teachers, lecturers, guardians and tutors as mentioned in Law No. 20 of 2003 on National Education System Article 1 point 6. Based on Government Regulation Number 19 Year 2005 on National Education Standards Article 28 point 3 and Law of the Republic of Indonesia Number 14 Year 2005 regarding teachers and lecturers are presented four competencies of educators as learning agents covering pedagogic competence, personality competence, professional competence, and social competence . Competence is a set of knowledge, skills and behaviors that must be owned, experienced and mastered by teachers or lecturers in performing professional duties. Professional competence in the Regulation of the Minister of National Education No. 27 of 2008 includes a teacher of BK who mastered the concept and praxis assessment to understand the condition of needs, and the problem of the counselee; Master theoretical framework and praxis guidance and counseling; Designing guidance and counseling programs; Implement a comprehensive guidance and counseling program; Assessing the process and results of guidance and counseling activities; Have awareness and commitment to professional ethics; Mastering the concepts and praxis of research in counseling and guidance. The successful implementation of counseling and guidance services will be closely related to the implementation competencies of the BK teacher/counselor as the person providing the assistance, including the combination of knowledge, academic, personal qualities, and skills in helping.